Healthcare costs of transarterial chemoembolization in the treatment of hepatocellular carcinoma - Fateen, Waleed; Khan, Farooq; O’Neill, Richard; James, Martin; Ryder, Stephen; Aithal, Guruprasad (Dove Medical Press, 2017)
Background: A meta-analysis comparing drug-eluting beads transarterial chemoembolization (DEB-TACE) with conventional transarterial chemoembolization (cTACE) has recently been published. On balance, no significant differences were found in terms of objective response and overall survival. The impact on healthcare costs had been studied in small series based on a hypothetical model and was in favor of DEB-TACE. We aimed to evaluate and compare healthcare costs and effectiveness of both modalities in a cohort of patients from Nottingham, UK. Methods: Using a dedicated radiology database, we identified all patients who had undergone cTACE or DEB-TACE between 2006 and 2012 at a single tertiary referral center based in Nottingham. We collected clinical data, including treatment response, postprocedure complications and 30-day mortality. Costing models were constructed to present both our local hospital perspective as well as the national health service position. Results: During our study period, 101 procedures were performed on 43 patients (76 cTACE procedures on 26 patients and 25 DEB-TACE procedures on 17 patients). Overall, 11/26 in cTACE and 5/17 in DEB-TACE group had progressive disease (p=0.52). Adverse events were seen in 6/76 cTACE compared with 7/25 DEB-TACE group (p=0.16). Based on the predetermined standard pathway there was an unadjusted average cost difference of £3770.30 (TACE =£9070.44, DEB-TACE =£5300.14) in favor of the DEB-TACE. Results from our costing models indicated a £2715.33 (95% CI £580.88–4849.77) cost difference in favor of the same procedure. Conclusions: Even when the extra costs of DEB-TACE were considered, the overall treatment costs per patient were lower in relation to cTACE.